Perovskite solar cell and chemical induction surface reconstruction preparation method
The use of chlorinated hydrocarbon or bromine hydrocarbon molecular modification layers in perovskite solar cells through chemically induced surface reconstruction method has solved the problem of perovskite absorbing layer defects, improved the photoelectric conversion efficiency and stability, and achieved high-performance calcium Preparation of titanium ore solar cells.
Patent Information
- Application Number
- CN202411279290.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
The light-absorbing layer of perovskite solar cells has a large number of defects, resulting in low photoelectric conversion efficiency and poor stability, limiting its commercial application.
Using chemically induced surface reconstruction method, chlorinated hydrocarbons or bromine hydrocarbon molecules are spin-coated on the perovskite absorption layer. Through halogen exchange reaction during annealing, a chlorine or bromide ion modification layer is formed, surface defects are passivated, and the interface is optimized. Charge transfer.
It significantly reduces trap density and non-radiated charge recombination, improves the photoelectric conversion efficiency and stability of perovskite solar cells, and improves battery performance.
Smart Images

Figure CN119136619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a perovskite solar cell and a preparation method for chemically induced surface reconstruction. Background Art
[0002] In the past few decades, perovskite solar cells have made significant progress in both laboratory and commercialization, showing great commercial potential. The power conversion efficiency of organic-inorganic hybrid perovskite solar cells has exceeded 26%, which is comparable to silicon solar cells. However, the presence of a large number of defects in the light-absorbing layer of perovskite solar cells limits their application in commercialization. Regardless of the method used to prepare the perovskite light-absorbing layer, there will be various defects on the surface. These defects are the central sites of non-radiative recombination, which can easily cause the photoelectric conversion efficiency of perovskite solar cells to decrease and the stability to be poor. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a perovskite solar cell and a method for preparing a chemically induced surface reconstruction to solve the problem that the perovskite light-absorbing layer is prone to defects, resulting in low photoelectric conversion efficiency and poor stability of the perovskite solar cell.
[0004] In order to achieve the above object, the present invention adopts the following technical solutions:
[0005] A method for preparing a chemically induced surface reconstruction of a perovskite solar cell comprises the following steps:
[0006] S1, sequentially preparing a first interlayer and a perovskite absorption layer on a conductive glass, wherein the anion in the perovskite absorption layer is iodine or bromine; and the first interlayer is a hole transport layer or an electron transport layer;
[0007] S2, spin coating or depositing a surface reconstruction layer precursor solution on the perovskite absorption layer, and preparing the surface reconstruction layer after annealing, wherein the surface reconstruction layer precursor solution is prepared by adding chlorinated hydrocarbon or brominated hydrocarbon molecules to an organic solvent, stirring and dissolving; during the annealing process, the chlorine in the chlorinated hydrocarbon is exchanged with part of the iodine or bromine in the perovskite absorption layer, or the bromine in the brominated hydrocarbon is exchanged with part of the iodine in the perovskite absorption layer;
[0008] S3, sequentially preparing a second interlayer and an electrode on the surface reconstruction layer; when the first interlayer is a hole transport layer, the second interlayer is an electron transport layer, and when the first interlayer is an electron transport layer, the second interlayer is a hole transport layer.
[0009] A further improvement of the present invention is:
[0010] Preferably, in S2, the concentration of the surface reconstruction layer precursor solution is 1-30 mg / mL.
[0011] Preferably, in S2, the surface reconstruction layer precursor solution is spin-coated on the perovskite absorption layer, the spin-coating speed is 1000-6000 rpm / min, and the spin-coating time is 10-70 s.
[0012] Preferably, in S2, the annealing temperature is 70-120° C., and the annealing time is 5-30 min.
[0013] A perovskite solar cell prepared by any of the above preparation methods comprises a conductive glass, a hole transport layer, a perovskite absorption layer, a surface reconstruction layer, an electron transport layer and an electrode arranged in sequence from bottom to top;
[0014] Or comprising a conductive glass, an electron transport layer, a perovskite absorption layer, a surface reconstruction layer, a hole transport layer and an electrode arranged in sequence from bottom to top;
[0015] When the anion in the perovskite absorption layer is iodine, the perovskite absorption layer contains bromine or chlorine; the surface reconstruction layer is a chlorinated hydrocarbon or a brominated hydrocarbon, containing iodine;
[0016] When the anion in the perovskite absorption layer is bromine, the perovskite absorption layer contains chlorine; the surface reconstruction layer is a chlorinated hydrocarbon and contains chlorine.
[0017] Preferably, the electron transport layer is TiO2, SnO2, (6,6)-phenyl-C61-butyric acid methyl ester, C 60 , Nb2O3, 1,3,5-tri-(N-phenyl-imidazol-2-yl)benzene or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline;
[0018] The thickness of the electron transport layer is 20-50 nm.
[0019] Preferably, the perovskite absorption layer is an ABX3 perovskite film, wherein A is any one or more of cesium, formamidine, and methylamine, B is any one or more of lead and tin, and X is one or more of I or Br;
[0020] The thickness of the perovskite absorption layer is 300-800 nm.
[0021] Preferably, the hole transport layer is any one of nickel oxide, WO3, MoO3, poly(9-vinylcarbazole), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 3-hexylthiophene polymer, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid, CuSCN, N′-di(phenyl)benzidine, 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphine or [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid;
[0022] The thickness of the hole transport layer is 10-60 nm.
[0023] Preferably, the electrode is a carbon electrode or a metal electrode.
[0024] Preferably, the metal electrode is any one of Au, Ag, Cu, ITO or IZO.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention discloses a method for preparing high-performance perovskite solar cells by chemically induced surface reconstruction. By introducing a chlorinated hydrocarbon or brominated hydrocarbon molecule modification layer on the surface of the perovskite film, the present invention proposes that the chlorinated hydrocarbon or brominated hydrocarbon molecules can be induced in situ to react with the Pb on the surface of the perovskite. 2+ Interaction occurs, forming new compounds on the surface of the perovskite layer, accompanied by the simultaneous incorporation of chlorine or bromide ions, replacing iodine or bromine or incorporating them into the crystal lattice. The bifunctional reaction optimizes the interfacial charge transfer, passivates the surface defects of the perovskite, significantly reduces the trap density and non-radiative charge recombination, improves the photoelectric conversion efficiency of perovskite solar cells, and reduces the impact of the external environment on the tolerance of perovskite solar cells, thereby effectively reducing the defects of the perovskite film and improving the stability of the perovskite film, significantly improving the battery performance.
[0027] The chlorine in the chlorinated hydrocarbon is exchanged with a small amount of iodine or bromine in the perovskite absorption layer, or the bromine in the brominated hydrocarbon is exchanged with part of the iodine in the perovskite absorption layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The mass spectrum of the substance prepared for Example 2 of the present invention;
[0029] Figure 2 X-ray diffraction patterns of Comparative Example 1 and Examples 1 to 3;
[0030] Figure 3PL spectra of CsPbI3 perovskite films prepared in Example 2 and Comparative Example 1;
[0031] Figure 4 TRPL spectra of CsPbI3 perovskite films prepared in Example 5 and Comparative Example 1;
[0032] Figure 5 Comparison of JV curves of CsPbI3 perovskite solar cells prepared in Examples 1 to 3 and Comparative Example 1;
[0033] Figure 6 is an operation stability diagram of the CsPbI3 perovskite solar cell prepared in Example 2 and Comparative Example 1 at the maximum power point;
[0034] Figure 7 It is a comparison diagram of the JV curves of the FAPbI3 perovskite solar cells prepared in Example 4 and Comparative Example 2. DETAILED DESCRIPTION
[0035] In order to solve the above technical problems, the first aspect of the present invention discloses a method for preparing high-performance perovskite solar cells by chemically induced surface reconstruction, wherein a surface reconstruction layer is prepared on the perovskite absorption layer, and the surface reconstruction layer is a chlorinated hydrocarbon or brominated hydrocarbon molecule deposited on the perovskite absorption layer by spin coating; the specific reaction process is to spin coat the surface reconstruction layer precursor on the perovskite absorption layer, and a halogen exchange reaction based on the SN2 mechanism is carried out during the annealing process. This reaction is an equilibrium reaction, and the reaction of converting chlorinated hydrocarbons or brominated hydrocarbons into iodinated hydrocarbons in an alcohol / acetone solvent is as follows:
[0036]
[0037] X is I ion, A is Cl or Br ion, and Y is Pb or Sn ion. This reaction is applied in perovskite solar cells. On the one hand, the I in the PbI2-rich perovskite surface is replaced by Cl or Br ions in chlorinated or brominated hydrocarbon molecules to passivate the defects on the surface of the perovskite film. On the other hand, Cl replaces iodide or bromide to form chlorine-substituted perovskite, or bromine replaces iodine to stabilize the surface structure of the perovskite.
[0038] The chlorocarbon or bromocarbon molecule modification layer is obtained by depositing chlorocarbon molecules or bromocarbon molecules on the perovskite absorption layer by spin coating or thermal evaporation.
[0039] The chlorinated hydrocarbon or brominated hydrocarbon molecule contains at least one or both of chlorine atoms and bromine atoms.
[0040] The method is applicable to both formal perovskite as well as trans-perovskite structures.
[0041] In some embodiments of the present invention, a method for preparing an inverse perovskite is disclosed, comprising the following steps:
[0042] Step 1, pre-treating the conductive glass;
[0043] Step 2, preparing a first interlayer on the conductive glass, the first interlayer is a hole transport layer, the thickness of the hole transport layer is 10 to 60 nm, and a hole transport layer solution with a concentration of 1 to 30 mg / mL is spin-coated on the transparent conductive glass and then annealed; the material of the hole transport layer is nickel oxide, WO3, MoO3, poly (9-vinyl carbazole), poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine], 3-hexylthiophene polymer, poly (3,4-ethylenedioxythiophene) -polystyrene sulfonic acid, CuSCN, N '-di Any one of (phenyl)benzidine, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphine, and [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid; the spin coating speed is 1000-5000 rpm / min, the time is 40s, and the annealing temperature is 100-200°C, and the time is 10-40min.
[0044] Step 3, preparing a perovskite absorption layer on the hole transport layer, the thickness of the perovskite absorption layer is 300-800nm, which is formed by spin coating a perovskite precursor solution on the hole transport layer and then annealing; the perovskite precursor solution is a mixed solution of dimethylformamide and dimethyl sulfoxide as a solvent, and the concentration of the perovskite precursor solution is 0.5-1.5mol / L; the spin coating is divided into two stages: the first stage has a rotation speed of 500-1500rpm / min and a time of 5-30s, and the second stage has a rotation speed of 2000-5000rpm / min and a time of 30-50s; the annealing temperature is 100-210°C and the time is 5-40min.
[0045] The perovskite absorption layer is an ABC3 perovskite film with a perovskite structure, wherein A is a cesium ion (Cs + ), formamidinium ion (FA + ), methylamine ion (MA + ), B is any one or more of lead ion and tin ion, X is a halogen anion (Br - or I - ) any one or more.
[0046] Step 4, prepare a surface reconstruction layer on the perovskite absorption layer, the preparation process is: add chlorinated hydrocarbon molecules or brominated hydrocarbon molecules to an organic solvent, stir until dissolved, and then prepare a surface reconstruction layer precursor solution; spin-coat the surface reconstruction layer precursor solution on the perovskite absorption layer, and anneal at 70-120°C for 5-30 minutes after spin coating; wherein the organic solvent is any one of isopropanol and acetone. Preferably, the concentration of chlorinated hydrocarbon or brominated hydrocarbon in the solution is 1-30 mg / mL, the spin coating speed is 1000-6000 rpm / min, and the time is 10-70s.
[0047] Specifically, the chlorinated hydrocarbon molecules can be: benzyl chloromethyl sulfide, bis(chloromethyl) sulfide, p-chlorophenol, 1,2-dichloroethane, p-chloroaniline, 1-chloro-N,N-dimethyl-2-propylamine, o-chloroaniline, 2-nitrobenzene sulfide, polyepichlorohydrin, phenylphosphonic dichloride, and the like.
[0048] Brominated hydrocarbon molecules can be: bromomethyl methyl ether, 3-bromomethylthiophene, p-bromophenol, 1,2-dibromobutane, epibromopropane, ambroxol, 6-bromothiochroman-4-one, 2,5-dibromoaniline, 2-amino-4-bromobenzoic acid, benzyl bromide, etc.
[0049] In the above process, chlorinated hydrocarbon molecules can replace perovskites where X is I or Br, while brominated hydrocarbon molecules can only replace perovskites where X is I.
[0050] Step 5, preparing a second interlayer on the surface reconstruction layer, the second interlayer is an electron transport layer, the thickness of the electron transport layer is 20 to 50 nm, and the electron transport layer solution with a concentration of 1 to 20 mg / mL is directly spin-coated on the passivation molecular modification layer; wherein the material of the electron transport layer is TiO2, SnO2, ZnO, (6,6)-phenyl-C61-butyric acid methyl ester (PCBM), C 60 , Nb2O3, 1,3,5-tri-(N-phenyl-imidazole-2-yl)benzene or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; the spin coating speed is 2000-4000 rpm / min, the time is 20-40s, the annealing temperature is 60-210°C, and the time is 10-30min.
[0051] Step 6: preparing an electrode on the electron transport layer, wherein the electrode is a carbon electrode or a metal electrode, and the metal electrode is any one of Au, Ag, Cu, ITO or IZO.
[0052] In some embodiments of the present invention, a method for preparing a formal perovskite is disclosed. The difference between this preparation method and the inverse perovskite is that the first interlayer in the above step 2 is an electron transport layer, and the preparation steps and parameters of the electron transport layer are the same as those of the above step 4; the second interlayer in the above step 4 is a hole transport layer, and the preparation steps and parameters of the hole transport layer are the same as those of the above step 2.
[0053] Based on the above preparation method, the second aspect of the present invention provides a perovskite solar cell prepared by the above preparation method, comprising a transparent conductive glass, a hole transport layer, a perovskite absorption layer, a surface reconstruction layer, an electron transport layer, a metal electrode or a carbon electrode stacked in sequence from bottom to top, or comprising a transparent conductive glass, an electron transport layer, a perovskite absorption layer, a surface reconstruction layer, a hole transport layer and a metal electrode or a carbon electrode stacked in sequence from bottom to top.
[0054] In the final perovskite solar cell, the content of the substitution element (chlorine or bromine) in the perovskite absorption layer is very small, only a small amount of iodine or bromine is replaced, and the corresponding surface reconstruction layer contains a small amount of iodine.
[0055] The following is further described in conjunction with specific embodiments.
[0056] Example 1
[0057] The perovskite solar cell structure of this embodiment is a transparent conductive glass, a hole transport layer, a perovskite absorption layer, a surface reconstruction layer, an electron transport layer and a metal electrode stacked in sequence from bottom to top, and its preparation method includes the following steps:
[0058] Step 1: Ultrasonic clean the FTO conductive glass in acetone, ethanol, and isopropanol for 20 minutes each to obtain clean FTO conductive glass.
[0059] Step 2: Disperse nickel oxide nanoparticles in deionized water to prepare a nickel oxide solution with a concentration of 10 mg / mL, and then spin-coat the solution on the FTO conductive glass at a spin-coating speed of 5000 rpm / min for 60 s; after spin-coating, anneal at 150°C for 30 min to obtain a hole transport layer.
[0060] Step 3: Dissolve CsI, DMAI and PbI2 in a mixture of dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 in a molar ratio of 1:1:1, place on a stirring table and stir for more than 12 hours to obtain a CsPbI3 perovskite precursor solution with a concentration of 1 mol / L; spin-coat the prepared CsPbI3 perovskite precursor solution on the hole transport layer prepared in step 2 at a spin-coating speed of 3000 rpm / min for 60 seconds; anneal at 200°C for 10 minutes after spin-coating to obtain a perovskite absorption layer.
[0061] Step 4: Add benzyl chloromethyl sulfide molecules to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 5 mg / mL, and then evenly spin-coat the solution on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, drop 100uL of the above solution onto the perovskite layer. After spin coating, anneal at 70°C for 10 minutes in a nitrogen environment to obtain a chemically induced surface reconstruction molecular modification layer.
[0062] Step 5: Spin-coat a 20 mg / mL PCBM chlorobenzene solution directly on the passivation molecular modification layer at a speed of 4000 rpm / min for 40 seconds to obtain an electron transport layer with a thickness of 40 nm. Step 6: Evaporate a 150 nm thick Ag film on the electron transport layer of step 5. The battery area is 0.09 cm 2 , and an inverse perovskite solar cell is obtained.
[0063] Example 2
[0064] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0065] The other steps are the same as those in Example 1.
[0066] Example 3
[0067] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 20 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0068] The other steps are the same as those in Example 1.
[0069] Example 4
[0070] In step 3 of this embodiment, FAI and PbI2 are dissolved in a mixture of dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 in a molar ratio of 1:1, and the mixture is stirred on a stirring table for more than 12 hours to obtain a FAPbI3 perovskite precursor solution with a concentration of 1 mol / L; the prepared FAPbI3 perovskite precursor solution is spin-coated on the hole transport layer prepared in step 2, and the spin coating process is divided into two stages: the first stage has a rotation speed of 1000 rpm / min and a spin coating time of 10 s; the second stage has a rotation speed of 4000 rpm / min and a spin coating time of 30 s; the annealing process is annealing at 150°C on a hot stage for 15 min to prepare a perovskite absorption layer.
[0071] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0072] The other steps are the same as those in Example 1.
[0073] Example 5
[0074] In step 4 of this embodiment, bis(chloromethyl) sulfide molecules are added to isopropanol to prepare a bis(chloromethyl) sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0075] The other steps are the same as those in Example 1.
[0076] Example 6
[0077] In step 4 of this embodiment, bis(chloromethyl) sulfide molecules are added to isopropanol to prepare a bis(chloromethyl) sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0078] The other steps are the same as those in Example 4.
[0079] Example 7
[0080] In step 4 of this embodiment, 3-bromomethylthiophene molecules are added to isopropanol to prepare a 3-bromomethylthiophene solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in a dynamic spin coating, with a rotation speed of 5000 rpm / min and a time of 60 s; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0081] The other steps are the same as those in Example 4.
[0082] Example 8
[0083] In step 4 of this embodiment, bromomethyl methyl ether molecules are added to isopropanol to prepare a bromomethyl methyl ether solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in a dynamic spin coating, with a rotation speed of 5000 rpm / min and a time of 60 s; when the substrate rotation speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0084] The other steps are the same as those in Example 4.
[0085] Example 9
[0086] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 1 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 1000 rpm / min for 50 seconds; when the substrate speed reaches 1000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 80°C in a nitrogen environment for 20 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0087] Example 10
[0088] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 30 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 6000 rpm / min for 10 seconds; when the substrate speed reaches 6000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 120° C. in a nitrogen environment for 5 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0089] Embodiment 11
[0090] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 20 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a rotation speed of 5000 rpm / min for 30 s; when the substrate rotation speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer, and after spin coating, it is annealed at 100° C. in a nitrogen environment for 5 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0091] Example 12
[0092] In step 3 of this embodiment, MABr and PbBr2 are dissolved in a mixture of dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 1:1, and stirred on a stirring table for more than 12 hours to obtain a MAPbBr3 perovskite precursor solution with a concentration of 1 mol / L; the prepared MAPbBr3 perovskite precursor solution is spin-coated on the hole transport layer prepared in step 2, and the spin-coating process is divided into two stages: the first stage speed is 1000rpm / min, and the spin-coating time is 10s; the second stage speed is 4000rpm / min, and the spin-coating time is 30s; then 300μL of chlorobenzene is dripped on the rotating substrate as an anti-solvent. The annealing process is 100℃ hot stage annealing for 10min to prepare the perovskite absorption layer.
[0093] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0094] Example 13
[0095] In step 3 of this embodiment, FABr and SnBr2 are dissolved in a mixture of dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 in a molar ratio of 1:1, and stirred on a stirring table for more than 12 hours to obtain a FASnBr3 perovskite precursor solution with a concentration of 1 mol / L; the prepared FASnBr3 perovskite precursor solution is spin-coated on the hole transport layer prepared in step 2, and the spin-coating process is divided into two stages: the first stage speed is 1000rpm / min, and the spin-coating time is 10s; the second stage speed is 4000rpm / min, and the spin-coating time is 30s; then 300μL of chlorobenzene is dripped on the rotating substrate as an anti-solvent. The annealing process is annealing at 100℃ hot stage for 10min to prepare the perovskite absorption layer.
[0096] In step 4 of this embodiment, benzyl chloromethyl sulfide molecules are added to isopropanol to prepare a benzyl chloromethyl sulfide solution with a concentration of 10 mg / mL, and then the solution is evenly spin-coated on the perovskite absorption layer in dynamic spin coating at a speed of 5000 rpm / min for 60 seconds; when the substrate speed reaches 5000 rpm / min, 100 uL of the above solution is dropped onto the perovskite layer. After spin coating, annealing is performed at 70°C in a nitrogen environment for 10 minutes to obtain a chemically induced surface reconstruction molecular modification layer.
[0097] Embodiment 14
[0098] The perovskite solar cell structure of this embodiment is a transparent conductive glass, an electron transport layer, a perovskite absorption layer, a surface reconstruction layer, a hole transport layer and a metal electrode stacked in sequence from bottom to top, and its preparation method includes the following steps:
[0099] Step 1: Ultrasonic clean the FTO conductive glass in acetone, ethanol, and isopropanol for 20 minutes each to obtain clean FTO conductive glass.
[0100] Step 2: preparing an electron transport layer 2 on the cleaned transparent conductive glass 1;
[0101] On a clean conductive glass substrate, an electron transport layer is prepared by water bath precipitation, spin coating, blade coating, atomic layer deposition or physical vapor deposition, and the material of the electron transport layer is any one of TiO2, ZnO, SnO2 or Nb2O5;
[0102] Steps 3 and 4 are the same as Steps 3 and 4 in Example 1.
[0103] Step 5: 90 mg Spiro-OMeTAD, 22 μL LiTFSI solution (520 mg LiTFSI powder dissolved in 1 mL acetonitrile) and 36 μL 4-tert-butylpyridine (tBP) were added to 1 mL chlorobenzene (CB), stirred for 12 hours and filtered to obtain 90 mg / mL lithium salt-doped hole transport layer (Spiro-OMeTAD) solution; the lithium salt-doped hole transport layer was spin-coated on the perovskite layer by spin coating; the spin coating speed was 5000 rpm / s, and the spin coating time was 30 s to prepare a hole transport layer;
[0104] Step 6: Evaporate a 150nm thick Au film on the hole transport layer of step 5, with a cell area of 0.09cm 2 , and we get the formal perovskite solar cell.
[0105] Comparative Example 1
[0106] In Example 1, the structure of the perovskite solar cell does not contain a chemically induced surface reconstruction molecular modification layer, and the preparation process of the chemically induced surface reconstruction molecular modification layer is omitted in the preparation method, and the other preparation steps are the same as in Example 1.
[0107] Comparative Example 2
[0108] In Example 4, the structure of the perovskite solar cell does not contain a chemically induced surface reconstruction molecular modification layer, and the preparation process of the chemically induced surface reconstruction molecular modification layer is omitted in the preparation method, and the other preparation steps are the same as those in Example 4.
[0109] The perovskite solar cells prepared in the above examples 1 to 8 and comparative examples 1 and 2 were characterized respectively. Figures 5-6 And Table 1.
[0110] Figure 1 In Example 2, the occurrence of the reaction was confirmed by mass spectrometry. Lead iodide and benzyl chloromethyl sulfide were mixed and stirred evenly and then tested. When Cl ions replaced I ions, the charge-to-mass ratio was 246, and this product was detected from the spectrum, thus confirming the occurrence of the reaction.
[0111] Figure 2 The X-ray diffraction diagrams of Comparative Example 1 and Examples 1 to 3 are shown in the figure. As shown in the figure, as the concentration of benzyl methyl sulfide increases, the position of the diffraction peak shifts to a larger angle, and this phenomenon occurs because the radius of Cl ions is smaller than that of I ions. This further verifies the occurrence of the reaction.
[0112] Figure 3PL spectra of CsPbI3 perovskite films prepared in Example 2 and Comparative Example 1. As shown in the figure, compared with Comparative Example 1, the inorganic CsPbI3 perovskite film after benzyl chloromethyl sulfide passivation treatment in Example 2 has a stronger PL emission peak and a slight blue shift, which indicates that the non-radiative recombination on the film surface is suppressed and the defects are reduced.
[0113] Figure 4 TRPL spectra of CsPbI3 perovskite films prepared in Example 5 and Comparative Example 1. As shown in the figure, compared with Comparative Example 1, the average charge lifetime of the inorganic CsPbI3 perovskite film after bis(chloromethyl) sulfide passivation treatment in Example 5 increased from 20 nanoseconds to 80 nanoseconds, indicating that bis(chloromethyl) sulfide treatment can effectively inhibit non-radiative charge recombination and passivate defects.
[0114] Figure 5 Table 1 is a comparison of the JV curves of the CsPbI3 perovskite solar cells prepared in Examples 1 to 3 and Comparative Example 1. As shown in the figure, compared with Comparative Example 1, the efficiency of Examples 1 to 3 is improved after adding the chemically induced surface reconstruction molecular modification layer. In particular, the efficiency of the device prepared in Example 2 is the highest, and the corresponding PCE is increased from 18.50% to 20.82%, which is also one of the highest efficiencies among all trans-inorganic perovskite solar cells currently available. In Example 3, further increasing the amount of benzyl chloromethyl sulfide will lead to a decrease in device performance, which may be because the excessive concentration of benzyl chloromethyl sulfide reduces the quality of the film.
[0115] Table 1 Performance parameters of perovskite solar cells prepared in comparative examples and examples
[0116] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA cm -2 )]]> FF(%) PCE(%) Comparative Example 1 1.08 20.78 82.2 18.50 Example 1 1.13 20.79 84.9 19.98 Example 2 1.17 20.79 85.9 20.82 Example 3 1.15 20.76 85.3 20.38
[0117] Figure 6 The operation stability diagram of the CsPbI3 perovskite solar cell prepared in Example 2 and Comparative Example 1 at the maximum power point. As shown in the figure, after modification with the chemically induced surface reconstruction molecular modification layer, the initial efficiency can still be maintained at more than 95% after 1500 hours of operation, while the untreated CsPbI3 perovskite solar cell has only 40% of the initial efficiency, indicating that the operation stability of the device is greatly improved after modification with the chemically induced surface reconstruction molecular modification layer.
[0118] Figure 7 Table 2 is a comparison of the JV curves of the FAPbI3 perovskite solar cells prepared in Example 4 and Comparative Example 2. As shown in the figure, compared with Comparative Example 2, the efficiency of Example 4 is greatly improved after adding the chemically induced surface reconstruction molecular modification layer. This also confirms the universality of this method, which is applicable to perovskite solar cells with different band gaps.
[0119] Table 2 Performance parameters of perovskite solar cells prepared in comparative examples and examples
[0120] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA cm -2 )]]> FF(%) PCE(%) Comparative Example 2 1.12 25.50 80.50 23.09 Example 4 1.17 25.58 83.12 24.92
[0121] In other embodiments of the present invention,
[0122] The chlorinated hydrocarbon molecule can be any one of bis(chloromethyl) sulfide, p-chlorophenol, 1,2-dichloroethane, p-chloroaniline, 1-chloro-N,N-dimethyl-2-propylamine, o-chloroaniline, 2-nitrobenzenesulfonyl chloride, polyepichlorohydrin or phenylphosphonyl dichloride, and can directly replace the benzyl chloromethyl sulfide molecule of Example 1, and the specific content is not repeated here.
[0123] The brominated hydrocarbon molecule can be any one of 3-bromomethylthiophene, p-bromophenol, 1,2-dibromobutane, epibromopropane, ambroxol, 6-bromothiochroman-4-one, 2,5-dibromoaniline, 2-amino-4-bromobenzoic acid or benzyl bromide, which can directly replace the bromomethyl methyl ether of Example 8, and the specific content is not repeated here.
[0124] The materials of the electron transport layer in this embodiment are TiO2, SnO2, ZnO, C 60 Any one of Nb2O3, 1,3,5-tri-(N-phenyl-imidazol-2-yl)benzene or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline can directly replace the PCBM of Example 1, and the specific content will not be repeated here.
[0125] The material of the hole transport layer is WO3, MoO3, poly (9-vinyl carbazole), poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine], 3-hexylthiophene polymer, poly (3,4-ethylenedioxythiophene) -polystyrene sulfonic acid, CuSCN, N '-di (phenyl) benzidine, 2,2 ',7,7 '-tetra [N,N-di (4-methoxyphenyl) amino] -9,9 '-spirobifluorene, [2- (9H-carbazole-9-yl) ethyl] phosphonic acid, (2- (3,6-dimethoxy-9H-carbazole-9-yl) ethyl) phosphine, [4- (3,6-dimethyl-9H-carbazole-9-yl) butyl] phosphoric acid. It can directly replace the nickel oxide of Example 1, and the specific content is not repeated.
[0126] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a chemically induced surface reconstruction of a perovskite solar cell. It is characterized in that The following steps are involved: S1, sequentially preparing a first interlayer and a perovskite absorption layer on a conductive glass, wherein the anion in the perovskite absorption layer is iodine or bromine; and the first interlayer is a hole transport layer or an electron transport layer; S2, spin coating or depositing a surface reconstruction layer precursor solution on the perovskite absorption layer, and preparing the surface reconstruction layer after annealing, wherein the surface reconstruction layer precursor solution is prepared by adding chlorinated hydrocarbon or brominated hydrocarbon molecules to an organic solvent, stirring and dissolving; during the annealing process, the chlorine in the chlorinated hydrocarbon is exchanged with part of the iodine or bromine in the perovskite absorption layer, or the bromine in the brominated hydrocarbon is exchanged with part of the iodine in the perovskite absorption layer; S3, sequentially preparing a second interlayer and an electrode on the surface reconstruction layer; when the first interlayer is a hole transport layer, the second interlayer is an electron transport layer, and when the first interlayer is an electron transport layer, the second interlayer is a hole transport layer.
2. A method for preparing a perovskite solar cell by chemically induced surface reconstruction according to claim 1, It is characterized in that In S2, the concentration of the surface reconstruction layer precursor solution is 1-30 mg / mL.
3. The method for preparing a perovskite solar cell by chemically induced surface reconstruction according to claim 1, It is characterized in that In S2, a surface reconstruction layer precursor solution is spin-coated on the perovskite absorption layer, the spin-coating speed is 1000-6000 rpm / min, and the spin-coating time is 10-70 s.
4. The method for preparing a perovskite solar cell by chemically induced surface reconstruction according to claim 1, It is characterized in that In S2, the annealing temperature is 70 to 120° C., and the annealing time is 5 to 30 minutes.
5. A perovskite solar cell prepared by the preparation method according to any one of claims 1 to 4, It is characterized in that It includes a conductive glass, a hole transport layer, a perovskite absorption layer, a surface reconstruction layer, an electron transport layer and an electrode arranged in sequence from bottom to top; Or comprising a conductive glass, an electron transport layer, a perovskite absorption layer, a surface reconstruction layer, a hole transport layer and an electrode arranged in sequence from bottom to top; When the anion in the perovskite absorption layer is iodine, the perovskite absorption layer contains bromine or chlorine; the surface reconstruction layer is a chlorinated hydrocarbon or a brominated hydrocarbon, containing iodine; When the anion in the perovskite absorption layer is bromine, the perovskite absorption layer contains chlorine; the surface reconstruction layer is a chlorinated hydrocarbon and contains chlorine.
6. The perovskite solar cell according to claim 5, It is characterized in that The electron transport layer is TiO 2 SnO 2 、(6,6)-phenyl-C61-butyric acid methyl ester、C 60 , Nb 2 O 3 , any one of 1,3,5-tri-(N-phenyl-imidazol-2-yl)benzene or 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline; The thickness of the electron transport layer is 20-50 nm.
7. The perovskite solar cell according to claim 5, It is characterized in that The perovskite absorption layer is ABX 3 Perovskite film, wherein A is any one or more of cesium, formamidine, and methylamine, B is any one or more of lead and tin, and X is one or more of I or Br; The thickness of the perovskite absorption layer is 300-800 nm.
8. The perovskite solar cell according to claim 5, It is characterized in that The hole transport layer is nickel oxide, WO 3 、MoO 3 , poly(9-vinylcarbazole), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], polymer of 3-hexylthiophene, poly(3,4-ethylenedioxythiophene)-polystyrenesulfonic acid, CuSCN, N′-di(phenyl)benzidine, 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphine, or [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid; The thickness of the hole transport layer is 10-60 nm.
9. The perovskite solar cell according to claim 5, It is characterized in that The electrode is a carbon electrode or a metal electrode.
10. The perovskite solar cell according to claim 9, It is characterized in that The metal electrode is any one of Au, Ag, Cu, ITO or IZO.
